Risk management and contingency factors in a public educational institution - Fernandes, Thayná de Oliveira; Câmara, Renata Paes de Barros; Callado, Aldo Leonardo Cunha; Moreira, Caritsa Scartaty (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: The objective of this study was to examine the contingency factors that may affect risk management practices in a public Higher Education Institution (HEI). Methodology: This is a case study with a quantitative-qualitative approach. Twenty participants who performed risk management functions at the HEI were selected. To achieve the research objective, a questionnaire was used and analyzed using descriptive statistics, and a semi-structured interview was conducted, with analysis based on content analysis and the construction of word clouds. Results: The results relate to the analyzed contingency factors. In the external environment, regulation and the performance of control bodies stood out. In the organizational structure, the interference of intellectual capital and physical structure was observed. Regarding technology, the most relevant variable was data storage, along with the evident need for specialized risk management software. In the contingency factor "strategy", the improvement of management processes and the quality of resource use were identified as essential. In the "organizational size" factor, the strong influence of budgetary resources was noted. Finally, in the "organizational culture" factor, the need for greater internal cooperation among the institution's members was highlighted. Contributions of the Study: This research identified contingency factors and obstacles that hinder the improvement of risk management within the institution. It was observed that the lack of knowledge among those responsible for risk management, the absence of an adequate organizational structure, the need for technological improvements, and the lack of regulatory support in ensuring compliance with regulations represent significant challenges to effective risk management.